Do Civil Wars, Coups and Riots Have the Same Structural Determinants?. Issue 3 (4th May 2017) - Bodea, Cristina; Elbadawi, Ibrahim; Houle, Christian
ABSTRACT: The literature on political instability focuses on institutional and leader survival or outcomes like civil wars and coups. We suggest that this approach overlooks lower levels of instability and that isolating outcomes understates the likelihood that they are manifestations of similar structural determinants. We extend the notion of instability to encompass jointly but distinctly civil wars, coups, and riots. Our explanation focuses on the role of political institutions and the related ethnopolitical strife over state power. Using data from 1950 to 2007, we find that the three outcomes share some determinants such as a factional partial democracy and the exclusion from power of a large proportion of the population; the inverted U-shaped effect of political institutions is driven by a subset of semidemocracies; and there is a substitution relationship between civil wars and coups emerging from the composition of governing coalitions.